ON THE STUDY OF COST Warehousing in total LOGISTICS COSTS SYSTEM - , А. П. (Municipal economy of cities. Series: «Economy science», 2013)
The method of investigation of the costs of warehousing in the total costs of logistics systems for example, ME "KharkivKomunOchystVod." Providing proposals that reduce the cost of warehouse ME "KharkivKomunOchystVod"